Patient reported quality of life after helical IMRT based concurrent chemoradiation of locally advanced anal cancer. Issue 2 (August 2016) - Joseph, Kurian; Vos, Larissa J.; Warkentin, Heather; Paulson, Kim; Polkosnik, Lee-anne; Usmani, Nawaid; Tankel, Keith; Severin, Diane; Nijjar, Tirath; Schiller, Dan; Wong, Clarence; Ghosh, Sunita; et al.
Abstract: Background and purpose: Concurrent chemoradiation (CCRT) is the standard treatment for locally advanced anal canal carcinoma, although treatment-related side effects can affect patient quality of life (QOL). The purpose was to prospectively evaluate the effects of Tomotherapy (HT) based CCRT on patient reported QOL in locally advanced anal cancer. Patients and Methods: Fifty-four patients treated with HT and concurrent 5-fluorouracil/mitomycin-C underwent QOL evaluation at baseline, after treatment, and during follow-up with EORTC core (QLQ-C30) and colorectal (QLQ-CR29) questionnaires. The QOL scores at baseline and post-treatment were compared. Results: All C30 functional symptoms, except emotional and cognitive functioning, were impaired end-of-treatment and recovered by 3 months follow-up. The majority of symptom scores were worse end-of-treatment but recovered by 3 months except for fecal incontinence (FI), diarrhea, urinary incontinence (UI), and dyspareunia which persisted. FI returned to baseline at 12 months while diarrhea, UI, and dyspareunia persisted. Conclusions: Most impaired functions and symptoms following HT based CCRT were temporary and improved by 3 months post-therapy. Late complications affecting QOL were FI, sexual function, UI, and diarrhea. Our observations support routine use of IMRT and emphasize the significance of precise evaluation of sexual, urinary, and anorectal functions before starting CCRT and routine incorporation of QOL evaluations.